Checkpoint Inhibitors Modulate Plasticity of Innate Lymphoid Cells in Peripheral Blood of Patients With Hepatocellular Carcinoma - Heinrich, Bernd; Ruf, Benjamin; Subramanyam, Varun; Myojin, Yuta; Lai, Chunwei W.; Craig, Amanda J.; Fu, Jianyang; Xie, Changqing; Kroemer, Alexander; Greten, Tim F.; Korangy, Firouzeh (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILC) are a heterogeneous and plastic population of cells of the innate immune system. Their role in cancer and specifically in hepatocellular carcinoma is unraveling. The presence of ILCs in peripheral blood of HCC patients has not been explored yet. Their role and function in response to checkpoint inhibitor therapy have also not been explored. Here, we characterized ILCs in PBMC of HCC patients at baseline and after treatment with immune checkpoint inhibitors (ICI) by flow cytometry and single-cell sequencing. Characterization of ILC subsets in PBMCs of HCC patients showed a significant increase in ILC1 and a decrease in ILC3 frequencies. Single-cell RNA-sequencing identified a subgroup of NK-like ILCs which expressed cytotoxicity markers as well as NKp80/KLRF1. This KLRF1high NK-like population showed low abundance in patients with HCC and was enhanced after combined anti-CTLA-4 and anti-PD-1immunotherapy. Trajectory analysis placed this population in between ILC1 and ILC3 cells. The transcriptomic signature of KLRF1high NK-like ILCs was associated with better progression-free survival in large HCC cohorts. This study shows a previously unknown effect of ICI on the composition and plasticity of ILCS in peripheral blood. Thus, ILCs from PBMC can be used to study changes in the innate immune system under immunotherapy.